Comparison of noncontrast MRI magnetization transfer and T2‐Weighted signal intensity ratios for detection of bowel wall fibrosis in a Crohn's disease animal model. Issue 3 (13th December 2014) - Dillman, Jonathan R.; Swanson, Scott D.; Johnson, Laura A.; Moons, David S.; Adler, Jeremy; Stidham, Ryan W.; Higgins, Peter D.R.
<x xml:space="preserve">Abstract</x> Purpose To compare the abilities of magnetization transfer magnetic resonance imaging (MT‐MRI) and T2‐weighted signal intensity (T2WSI) ratios to detect intestinal fibrosis in a Crohn's disease animal model. Materials and Methods Ten rats ("Group 1") received one trinitrobenzenesulfonic acid enema to induce acute colonic inflammation, while 10 additional animals ("Group 2") received multiple enemas to induce colonic inflammation and fibrosis. Gradient recalled‐echo MT‐MRI (5 and 10 kHz off‐resonance) and T2‐weighted spin‐echo imaging were performed 2 days after the last enema. MT ratios (MTR) and T2WSI ratios were calculated in the area of greatest colonic thickening. Bowel wall MTR, bowel wall MTR normalized to paraspinous muscle MTR ("normalized MTR"), and T2WSI ratios were compared between animal groups using Student's t‐test. Results At 10 kHz off‐resonance, mean bowel wall MTR for Group 1 was 24.8 ± 3.1% vs. 30.3 ± 3.2% for Group 2 (P = 0.001). Mean normalized MTR was 0.45 ± 0.05 for Group 1 and 0.58 ± 0.08 for Group 2 (P = 0.0003). At 5 kHz off‐resonance, mean bowel wall MTR for Group 1 was 34.7 ± 5.2% vs. 40.3 ± 3.6% for Group 2 (P = 0.015). Mean normalized MTR was 0.53 ± 0.08 for Group 1 and 0.64 ± 0.07 for Group 2 (P = 0.003). Mean T2WSI ratio was 5.32 ± 0.98 for Group 1 and 3.01 ± 0.66 for group 2 (P < 0.0001). Mean T2WSI ratio/MTR (10 kHz off‐resonance) was 12.06 ± 2.70 for Group 1 and 5.22 ± 1.29 for Group 2 (P < 0.0001), with an ROC c‐statistic of 0.98. Conclusion MTR and T2WSI ratios detect bowel wall fibrosis in a Crohn's disease animal model. J. Magn. Reson. Imaging 2015;42:801–810.